Classificação Estrutural e Qualidade da Madeira do Clone GT 1 de Hevea brasiliensis Muell. Arg - Leonello, Elaine Cristina [UNESP]; Ballarin, Adriano Wagner [UNESP]; Ohto, Jéssica Monari [UNESP]; Palma, Hernando Alfonso Lara [UNESP]; Escobar, Javier Farago [UNESP] (FapUNIFESP (SciELO), 2012)
Latex is the main product extracted from rubber trees (Hevea brasiliensis). In Brazil, at the end of the production cycle of latex, the wood of rubber tree is traditionally used for energy purposes, but several international studies have reported consolidated practices of adding value to it. The objective of this paper was to evaluate the quality of wood and classify it structurally based on its mechanical properties. Six 20-year-old trees of the clone GT 1 of rubber tree proceeding from Itajobi, State of Sao Paulo, Brazil were sampled. Reduced dimensions specimens in the radial direction of the wood were produced to evaluate the quality by compression parallel to the grain, static bending and Janka hardness tests. Two specimens, one from the lower log (since the ground up to breast height) and one from the higher log (from breast height up to 2.50 m) were produced for structural classification of the wood based on the characteristic strength in compression parallel to the grain (NBR 7190 norm, 1997). The wood was classified as C40 (fc0k ≥ 40 MPa) class. Results revealed that the strength was not statistically different in the radial direction (except for the Janka hardness), though tending to increase from pith to bark.
Quality of Wood and Structural Classification of Hevea brasiliensis Clone GT 1
Keywords: Rubber tree.; Technology; Wood mechanical properties; Hevea brasiliensis